Critical Assessment 5: Thermodynamic data for vacancies. (November 2014) - Dinsdale, A. T.; Khvan, A. V.; Watson, A.
<x content-type="archive" xml:space="preserve">Abstract</x> The thermodynamic properties of crystalline phases are generally represented well in terms of the compound energy formalism and the model has been implemented in all the major software packages used to calculated phase equilibria. The formalism is particularly successful in modelling defects in crystals, both the formation of holes or vacancies on lattice sites, and the dissolution of atoms on interstitial sublattices. In the former case the formalism may require the definition of data for pure vacancy itself. In this assessment we investigate the possible values for the Gibbs energy of vacancy to be used in the compound energy formalism and show that a value of zero or negative will always lead to unwanted catastrophic stability of the phase.